2020
DOI: 10.1103/physrevd.101.076015
|View full text |Cite
|
Sign up to set email alerts
|

Novelty detection meets collider physics

Abstract: Novelty detection is the machine learning task to recognize data, which belong to an unknown pattern. Complementary to supervised learning, it allows to analyze data model-independently. We demonstrate the potential role of novelty detection in collider physics, using autoencoder-based deep neural network. Explicitly, we develop a set of density-based novelty evaluators, which are sensitive to the clustering of unknown-pattern testing data or new-physics signal events, for the design of detection algorithms. W… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
122
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 117 publications
(123 citation statements)
references
References 46 publications
1
122
0
Order By: Relevance
“…In terms of quantitative measures, we showed how to use the EMD to characterize the impact of detector effects and to calculate the intrinsic dimension of a jet ensemble. For qualitative studies, we showed how to use the EMD to identify the most representative jets in a histogram bin and the least representative jets in the ensemble as a whole, where the latter analysis is particularly interesting in the context of anomaly detection for new physics searches [171][172][173][174][175][176][177].…”
Section: Discussionmentioning
confidence: 99%
“…In terms of quantitative measures, we showed how to use the EMD to characterize the impact of detector effects and to calculate the intrinsic dimension of a jet ensemble. For qualitative studies, we showed how to use the EMD to identify the most representative jets in a histogram bin and the least representative jets in the ensemble as a whole, where the latter analysis is particularly interesting in the context of anomaly detection for new physics searches [171][172][173][174][175][176][177].…”
Section: Discussionmentioning
confidence: 99%
“…Part of these approaches use machine learning techniques, which is another direction into which new physics searches at the LHC can expand, as has been also proposed recently in several other contexts (e.g., refs. [34][35][36][37][38][39][40][41][42][43]).…”
Section: Discussionmentioning
confidence: 99%
“…• More recently, a variety of approaches have been proposed, often relying on sophisticated deep learning techniques, that attempt to be both signal and background model agnostic, to varying degrees. These include approaches based on autoencoders [26][27][28][29][30][31], weak supervision [32,33], nearest neighbor algorithms [34][35][36], probabilistic modeling [37], and others [38]. These are indicated in the upper-right corner of Fig.…”
Section: Bsm Sensitivitymentioning
confidence: 99%
“…Yet, they have varying degrees of both signal-model and background-model independence, as there is often a tradeoff between the broadness of a search and how sensitive it is to particular classes of signal scenarios. Existing and proposed model-agnostic searches range from fully-signal-model independent but fully-background model dependent [10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25] (because they compare data to SM simulation); to varying degrees of partial signal-model and background-model independence [26][27][28][29][30][31][32][33][34][35][36][37][38]. A comprehensive overview of existing model-agnostic approaches and how they are classified in terms of signal and background model independence will be given in Section 2.…”
Section: Introductionmentioning
confidence: 99%